1978
DOI: 10.1111/j.1464-410x.1978.tb04216.x
|View full text |Cite
|
Sign up to set email alerts
|

The Behaviour of the Bladder During Physical Activity

Abstract: The technical difficulties of obtaining reliable recordings of bladder, rectal and detrusor pressures from patients who are standing, walking or exercising have been largely overcome by a method described in this paper. The recordings help us to understand the behaviour of the lower urinary tract during physical activity and are of value in the diagnosis of urological problems, especially incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

1987
1987
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 2 publications
1
23
0
2
Order By: Relevance
“…Their muscles seem to be strong enough to prevent leakage during coughing but not when landing on a trampoline. James (1978) found that the highest bladder pressure occured during coughing. However, the occurrence of reflex pelvic muscular activity during cough has been reported (Constantinou & Govan, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Their muscles seem to be strong enough to prevent leakage during coughing but not when landing on a trampoline. James (1978) found that the highest bladder pressure occured during coughing. However, the occurrence of reflex pelvic muscular activity during cough has been reported (Constantinou & Govan, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Fluid filled catheters are adequate for the demands of conventional cystometry but are prone to artefacts caused by the acceleration of the liquid within the system on movement of the patient or equipment. In 1978, James overcame this by employing an air coupled system 8 . He used this in preference to a new type of measuring catheter, namely the microtransducer, with which he had experienced the problems of expense and high failure rates.…”
Section: Recording Devicesmentioning
confidence: 99%
“…Hence, the patients he investigated in Exeter were able to move more freely around the urodynamic laboratory and to perform a wide range of provocation exercises during UDS, particularly to demonstrate exercise‐induced stress urinary incontinence and detrusor overactivity. Dr James published the background to his methodology during the late 1970s . This not only described the advantages of AFCs during ambulant UDS, but also described the advantages of concurrently using an electronic perineal pad which approximately quantified the volume, but more importantly the timing, of urine losses and their relationship with urodynamic pressure changes .…”
Section: Introductionmentioning
confidence: 99%